Parapharyngeal Abscess in a Child: A Case Report - Pourmoshtagh, Hasan; Akbari Dailamaghani, Nader (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Parapharyngeal space abscess is a rare and life-threatening condition that is more prevalent in preschool children. Patients mostly are febrile with sore throat and torticoli. The diagnostic method of choice is a neck CT scan with contrast. Patients should be admitted and receive intravenous antibiotics with coverage of aerobic and anaerobic organism. Also, otolaryngology consultation for early surgery and drainage should be done. In this report, we presented a three and a half years old boy with fever, sore throat, and torticoli. Case presentation: A three and a half years old boy was referred to our hospital due to fever, sore throat, torticollis, neck lymphadenopathy, and poor feeding except receiving antibiotics, his symptoms didn’t change. Ultrasonography was done with multiple bilateral lymphadenopathies in submental, submandibular, and jugular proximities with the maximum sizes if 9 mm in the left side and 7 mm in the right side with no collections or abscess. In the CT scan there were a left parapharyngeal space abscess with spread to retropharyngeal and pressure effect on hypopharynx and another abscess in the same site. Surgical drainage of both abscesses was done and postoperative ICU admission with blood transfusion and intravenous antibiotics including meropenem, vancomycin, and metronidazole administered. Finally, the patient was discharged with a good condition and there was no complaint or problem in follow-ups. Discussion: Although this disease is life-threatening but, with early diagnosis and proper treatment, prognosis will be good. Delay in the diagnosis and treatment increases complication rate and can increase mortality rate to 40%. Conclusion: Retropharyngeal or parapharyngeal abscess is rare and life-threatening condition that physician should be aware about it.